An Enhancement of Bubble Sorting Algorithm - Harsh N, Nankani; Bhandari, Mukesh (International Journal of Computer Sciences and Engineering, 2025)
Sorting is an important technique of data structure which finds its place in many real-life applications. There are various sorting algorithms are in existence till date. In this paper, we have tried to improve upon execution time of the Bubble Sort algorithm by implementing the algorithm using an enhancement of it. An extensive analysis has been done by us on the new algorithm and the algorithm has been compared with the traditional method of Bubble Sort. Observations have been obtained on comparing this new approach with the existing approaches of Bubble Sort. The new proposed approach was tested for Average Case analysis, Best Case analysis and Worst case analysis. It has been analysed that the new approach has given very good results on Average Case and Worst Case analysis. The new approach was tested on random data of various ranges from small to large. It has been observed that the new approach has given efficient results in terms of execution time. Hence, we have reached to the conclusion through the experimental observations that the new algorithm given in this paper is better than the traditional Bubble Sort.